Electromyographical comparison of a traditional, suspension device, and towel pull-up - Snarr, R. L.; Hallmark, A. V.; Casey, J. C.; Esco, M. R. (Journal of Human Kinetics, 2017)
Strengthening muscles of the back may have various implications for improving functions of daily living, aiding in the transfer of power in throwing, and assist in injury prevention of the shoulder complex. While several versions of the pull-up exist, there is currently no literature comparing their differences. The purpose of this investigation was to compare the electromyographical activity of the latissimus dorsi, posterior deltoid, middle trapezius, and biceps brachii while performing three variations of the pull-up. Resistance-trained men and women (n =15, age = 24.87 ± 6.52 years) participated in this study by performing traditional pull-ups, suspension device pull-ups, and towel pull-ups in a randomized fashion. Each pull-up was performed for three repetitions with a 1.5 bi-acromial grip-width for each participant. Normalized (%MVC) electromyographical values were recorded for each muscle group during each pull-up variation. No significant differences existed within the latissimus dorsi, biceps brachii or posterior deltoid between any of the exercises. For the middle trapezius, towel pull-ups provided significantly lower muscle activity than the traditional pull-up, while no differences between suspension pull-ups and the other variations occurred. In conclusion, only one muscular difference existed between the exercise variations and all versions examined provided electromyographical values, determined by current literature, to invoke a sufficient stimulus to promote increases in muscle strength and hypertrophy. Although further research is needed, practitioners can be confident when programming any of the movement variations examined when attempting to elicit adaptations of muscular strength and hypertrophy.